Activated Human Umbilical Cord Blood Platelet-Rich Plasma Enhances the Beneficial Effects of Human Umbilical Cord Mesenchymal Stem Cells in Chemotherapy-Induced POF Rats - Jiawei Wang; Yunxiao Zhao; Fengque Zheng; Nana Ma; Rongyan Qin; Weili Qin; Bo Liu; Aiping Qin (Hindawi Limited, 2021)
Saving the ovarian function of premature ovarian failure (POF) patients undergoing chemotherapy is an important problem in the field of reproductive medicine. At present, human umbilical cord mesenchymal stem cells (HucMSCs) have been used in the treatment of POF, but the effect is still not optimal. The purpose of this study was to determine whether human umbilical cord blood platelet-rich plasma (ucPRP) enhances the beneficial effects of HucMSCs in the treatment of POF. First, we observed the effects of changes in the biological activity of ucPRP on HucMSCs in vitro. Subsequently, we tracked the distribution and function of the HucMSCs in POF rats, and the rats' estrus cycle and serum sex hormones, follicular development, ovarian angiogenesis, ovarian granulosa cell proliferation, and apoptosis were assessed. The results of the study showed that the addition of ucPRP in vitro accelerates proliferation and reduces apoptosis of the HucMSCs while upregulating the stemness gene of the HucMSCs. The combined transplantation of HucMSCs and ucPRP resulted in more stem cells being retained in the ovaries of POF rats, the estrus cycle of the POF rats being restored, the levels of serum E2, AMH, and FSH improving, and damaged follicles beginning to grow. Finally, we confirmed that the potential mechanism of the combination of HucMSCs and ucPRP to rescue the ovarian function of POF rats is to promote ovarian angiogenesis and to promote the proliferation and reduce the apoptosis of ovarian granulosa cells. The upregulation of AMH and FHSR expression and the downregulation of caspase-3 expression in granulosa cells are potential mechanisms for the recovery of ovarian function. Our research results suggest that the combined application of HucMSCs and ucPRP is a safe and efficient transplantation program for the treatment of POF, thus providing a reliable experimental basis for the clinical application of stem cell therapy in POF.